2007
DOI: 10.1111/j.1540-6210.2007.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Nature of Public Entrepreneurship

Abstract: Taïeb Hafsi is the Walter J. Somers Professor of International Strategic Management at HEC Montreal. He has written numerous articles and books dealing with strategic management and change in situations of complexity. He holds a master's degree in management from the Sloan School of Management at the Massachusetts Institute of Technology and a doctorate in business administration from Harvard Business School.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
0
21

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(153 citation statements)
references
References 53 publications
(84 reference statements)
3
129
0
21
Order By: Relevance
“…Most research emphasizes the role of MMs as key drivers of CE. For instance, MMs are identified as the most entrepreneurial people (Morris and Jones 1999), the largest group of initiators (Borins 2000), and the main source of creativity in entrepreneurship (Bernier and Hafsi 2007). Yet, this significant contribution of MMs cannot be taken for granted and cannot be understood in isolation of their TMT's influence.…”
Section: Discussionmentioning
confidence: 99%
“…Most research emphasizes the role of MMs as key drivers of CE. For instance, MMs are identified as the most entrepreneurial people (Morris and Jones 1999), the largest group of initiators (Borins 2000), and the main source of creativity in entrepreneurship (Bernier and Hafsi 2007). Yet, this significant contribution of MMs cannot be taken for granted and cannot be understood in isolation of their TMT's influence.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, economists (Nalebuff & Stiglitz, 1983;Wright, 1983;Rogerson, 1989) have long claimed that under certain conditions innovation prizes can induce innovation, that is, provide private entrepreneurs with strong incentives to invest in R&D. In particular, the interest has been in innovation prizes as an alternative to patent systems in invention appropriation (de Laat, 1996;Scotchmer, 2004;Masters, 2005;Hopenhayn, Llobet & Mitchell, 2006;Chari, Golosov & Tsyvinski, 2012;Clancy & Moschini, 2013). What literature there is on innovation awards has, however, been mainly confined to studies concerning the innovativeness of (public) management (Altshuler & Behn, 1997;Bernier & Hafsi, 2007;Borins, 2008) instead of the realm of technological innovation, where the majority of innovation studies are found (Kalil, 2006). Additionally, innovation awards and prizes have been used in choosing case studies and in delineating samples (Simmie, 2004;Gemünden, Salomo & Hölze, 2007) and as a measure of the support received and the successfulness of innovative activities at firm-level (Romijn & Albaladejo, 2002;Laforet, 2009).…”
Section: Foundations: Innovation Policy As Context For Awardsmentioning
confidence: 99%
“…However, it is clear, that in different situations some individuals will have better options or conditions that they can take advantage to create enterprises or develop innovative products or services through them. Bernier and Hafsi (2003) describe entrepreneurship as a process in which an agent manages to conceptualize and implement an idea, notion, service, product or activity. An entrepreneur is someone who is able to balance the economically desirable with the technologically/operationally feasible, someone who takes a calculated risk to seize an opportunity or meet unsatisfied needs in hope of establishing a sustainable business.…”
Section: Introductionmentioning
confidence: 99%